A PANEL OF MICROSATELLITE MARKERS FOR GENETIC DIVERSITY AND PARENTAGE ANALYSIS OF DOG BREEDS IN PAKISTAN - M. S. Tahir; T. Hussain; M. E. Babar; A. Nadeem; M. Naseer; Z. Ullah; M. Intizar; S. M. Hussain (Journal of Animal and Plant Sciences, 2015)
A molecular genetics tool comprised of a panel of 15 microsatellite markers was developed and used to investigate parentage and breed characterization of two most kept breeds of dogs including German shepherd and Labrador retriever in Pakistan. Blood samples of 20 dog families (10 from each breed) were collected from Army dog Breeding Training Center and School, Rawalpindi, Pakistan and Kennel Club of Pakistan. Genomic DNA was extracted by standard inorganic protocol. Microsatellite markers with high Polymorphism Information Content (PIC) and He (Hetrozygosity) values were selected and optimized into four multiplexes. Amplification reactions were followed by genotyping in 7% non-denaturing polyacrylamide gel electrophoresis (PAGE). Parentage analysis of 20 families using this panel of microsatellite markers was 100% successful. Average values of Polymorphism Information Content (PIC), Heterozygosity (He) and Combined Power of Exclusion (CPE) combined for both of the breeds were found to be 0.724, 0.6345 and 0.9998 respectively. Moreover, deviation from Hardy-Weinberg equilibrium equation was observed moderately for both dog breeds. Allelic frequencies for majority of the microsatellite markers between both dog breeds were clearly distinct. This study demonstrated the panel of 15 microsatellite markers could effectively validate parentage and breed characterization in dogs.
Keywords: Characterization; Parentage analysis; Microsatellite markers; Dog breeds; Pakistan